Effects of dry-land training in female swimmers - Leko, G.; Siljeg, K. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: According to the development plan of the Croatian Swimming Association, female swimmers aged 12 to 13 fall into the cadet or pre-junior category whose task is to train for competitions. The above implies inclusion dry-land training with the aim to improve strength, endurance and flexibility (Guy, 2000). The aim of the paper is to determine whether the six month dry-land training in swimming brings about positive results in female swimmers` basic motoric ability in the age group 12-13. Methods: The sample of subjects consisted of 29 female swimmers aged 12-13. All participants were in good health, and they had been involved in swimming training process for the last 6 years. They train six times per week in water and tree times per week they were conducting dry-land training . A variable sample includes 13 tests for the assessment of basic motor skills that measured: explosive power (4 tests), muscular strength endurance (4 tests) and flexibility (5 tests). Results: Statistic for Windows version 10.0 was used for the statistical analysis of specific motor skills. The following was computed: basic statistical parameters. The data was analyzed using MANOVA and ANOVA for repeated measurements to determine differences between measurements. Statistical significance was set at p < 0.05. Multivariate variant analysis showed a statistically significant improvement in the observed group of tests that define basic motoric abilities of female swimmers. A series of univariate analyses showed that only test for the assessment legs explosive power and endurance have a statistically significant improvement. Discussion: Results indicate insufficient dry-land training for trunk stability and upper body. Some autors (Šimek et al, 2002) in their paper indicates that arms and shoulders in women are the weakest link if viewed from the point of view of strength. In swimming, upper limbs make the biggest propulsion, and therefore it is necessary to increase their strenght , endurance and flexibility. Flexibility can maintain or increase joint range of motions, allowing for longer and more efficient strokes (Salo, 2008).